Groundwater models through stakeholders' eyes: Evaluating benefits, challenges, and lessons for SGMA implementation - Linda Söller; Laura Foglia; Thomas Harter (California Agriculture)
The Sustainable Groundwater Management Act (SGMA) requires stakeholder participation in developing groundwater sustainability plans (GSPs) to ensure the reliability of groundwater resources. Groundwater models became widely used in GSP development (e.g., to evaluate management actions). This study explores stakeholder perceptions of the benefits and challenges of using these models in GSP development and of models’ abilities to deal with uncertainties arising from existing data gaps. Qualitative interviews and minutes from groundwater advisory committee meetings from three groundwater basins reveal that groundwater models can improve stakeholders’ understanding of the groundwater system and help stakeholders identify management actions. However, model complexity and uncertainty in terms of hydrogeological processes and data gaps hinder stakeholders’ full understanding of the model development and results. Modelers should leverage stakeholder knowledge to build trust and collaboratively improve model accuracy through active participation in the modeling process. To prevent misunderstanding, future and ongoing processes should prioritize transparent communication about the model design, assumptions, and limitations. In general, SGMA’s regulatory process facilitates decision-making amid uncertainty and ensures lasting collaboration between modelers and stakeholders.